2012
DOI: 10.1111/j.1540-8183.2012.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Same Sitting Hybrid Coronary Artery Revascularization versus Off‐Pump Coronary Artery Bypass in Multivessel Coronary Artery Disease

Abstract: Same sitting HCR appears to be feasible and may offer superior outcomes to standard OPCABG, further studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(134 citation statements)
references
References 22 publications
2
129
0
3
Order By: Relevance
“…Among studies that compared intensive care and postoperative hospital length of stay between 1-stage HCR and conventional CABG, both time of recovery at the intensive care unit and time to discharge were shorter in the HCR group. 3,9,13 In our study, postprocedural length of hospital stay tended to be shorter after HCR than after CABG, but did not reach statistical significance. A number of reasons may be attributable to this finding: (1) the use of minimally invasive techniques was lower in our cohort than in others; (2) HCR occurred in a more heterogenous (and generally sicker) patient population; (3) HCR procedures performed do not only represent those performed by high-volume operators in specialized HCR centers but instead present an overall experience among US hospitals.…”
Section: Hospital Staymentioning
confidence: 67%
See 1 more Smart Citation
“…Among studies that compared intensive care and postoperative hospital length of stay between 1-stage HCR and conventional CABG, both time of recovery at the intensive care unit and time to discharge were shorter in the HCR group. 3,9,13 In our study, postprocedural length of hospital stay tended to be shorter after HCR than after CABG, but did not reach statistical significance. A number of reasons may be attributable to this finding: (1) the use of minimally invasive techniques was lower in our cohort than in others; (2) HCR occurred in a more heterogenous (and generally sicker) patient population; (3) HCR procedures performed do not only represent those performed by high-volume operators in specialized HCR centers but instead present an overall experience among US hospitals.…”
Section: Hospital Staymentioning
confidence: 67%
“…7,[9][10][11][12][13][14][15][16][17] In Table 4, we have summarized the key findings from these studies. The number of patients who underwent HCR in these studies ranged from 5 to 300 patients, and most operators used a partial sternotomy or a small lateral thoracotomy approach with or without the use of robotic assistance.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…20 The reported stroke rates were 0% to 1.7%. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] It is notable that despite the anaortic approach used for the HCR CABG arm (mostly in situ LIMA conduit), the stroke rates are not much lower.There are two meta-analyses that evaluate the studies done on HCR and conventional CABG patients (Table 2). 27,28 Phan and Harskamp both showed that there is no benefit for perioperative mortality, stroke, or 1-year freedom from major adverse events when using HCR over CABG.…”
mentioning
confidence: 99%
“…(128) Este tipo de procedimento pode diminuir o custo do tratamento, por reduzir o tempo de internação, minimizar os riscos da instabilização da placa da lesão coronariana não tratada e, consequentemente o aparecimento de uma SCA e a recorrência de internações hospitalares entre os procedimentos estagiados. (129)(130) Uma outra vantagem é a satisfação do paciente, uma vez que todo o procedimento é realizado em um único tempo, através de técnicas minimamente invasivas. (129,131) Uma das limitações desse tipo de tratamento, um é o equilíbrio entre a necessidade terapia de DAP para evitar a ocorrência de trombose dos stents, com o risco de sangramento cirúrgico.…”
Section: Diferentes Técnicas De Realizar a Rmhunclassified
“…(129,130,142,149) Nos pacientes submetidos a RMH, excelentes taxas de patência do enxerto de ATI -DA têm sido relatadas. (150) têm sido publicadas variando de 93% a 100% no pós operatório imediato, (130,133,140,144,146,151,152) e de 90% (139) a 94% (137) …”
Section: Terapia De Antiagregação Plaquetáriaunclassified